Self-biomineralized in situ injectable CaSO4 nanorods-enriched collagen-hyaluronic acid composite hydrogels for biomimetic bone reconstruction in a minimally invasive manner. (February 2023) - Liu, Xingzhu; Zhang, Yajie; Hussain, Zahid; Zheng, Penghui; Xu, Mingsheng; Zhao, Hongbo; Liu, Yuanshan; Cao, Yi; Ullah, Ismat; Osaka, Akiyoshi; Pei, Renjun
Highlights: In situ injectable collagen-hyaluronic acid (Col-HA) hydrogel embedded with calcium sulfate nanorods (CSN) was developed via a bio-orthogonal reaction. The formulated CSN@Col-HA composite hydrogels not only have the potential to enhance cell adhesion and proliferation, but also serve as the system to control Ca 2+ release. This composite hydrogels allow straightforward in situ injection and subsequent adaption of composite hydrogels to irregularly shaped bone defects. CSN-incorporated composite hydrogels facilitate self-biomineralization, thereby fast-forming bone-like hydroxyapatite (HAp) within the hydrogel. Ca 2+ release stimulates the differentiation of preosteoblasts, and promotes in situ bone growth. Abstract: In situ injectable natural polymer-based hydrogels can be utilized to fill irregular defects and promote tissue regeneration. However, most hydrogels showed limited ability for self-biomineralization and can not guide the formation of new bone. Herein, according to the challenges encountered in advancing materials to clinical research, an injectable collagen-hyaluronic acid (Col-HA) hydrogel embedded with calcium sulfate nanorods (CSN) was developed via a bio-orthogonal reaction between norbornene (Nb) and tetrazine (Tz). The formulated CSN@Col-HA composite hydrogels not only have the potential to enhance cell adhesion and proliferation, but also serve as the system to control Ca 2+ release. This composite hydrogel displayed impressive injectability, allowing straightforward in situ injection and subsequent adaption of composite hydrogels to irregularly shaped bone defects. CSN-incorporated composite hydrogels facilitate self-biomineralization, thereby fast-forming bone-like hydroxyapatite (HAp) within the hydrogel. Furthermore, Ca 2+ released in a steady and sustained way from the composite hydrogels stimulated the differentiation of preosteoblasts, and promoted in situ bone growth. Our findings suggested that CSN@Col-HA composite hydrogels can successfully mediate the optimized CSN degradation, effectively accelerate HAp formation, and boost in situ bone development via the minimally invasive application. Graphical abstract: Image, graphical abstract